Production of Monocyte Chemoattractant Protein 1 in Tuberculosis Patients - Lin, YuanGuang (American Society for Microbiology, 1998)
To investigate the role of monocyte chemoattractant protein 1 (MCP-1) in the immune response to Mycobacterium tuberculosis, we studied MCP-1 production in tuberculosis patients. CD14(+) blood monocytes from tuberculosis patients spontaneously expressed higher levels of MCP-1 mRNA and protein than CD14(+) monocytes from healthy tuberculin reactors. MCP-1 production in lymph nodes from tuberculosis patients was also markedly increased. These findings suggest that MCP-1 can contribute to the antimycobacterial inflammatory response by attracting monocytes and T lymphocytes.